THE ASSESSMENT OF PROJECT WORKS AT HIGHER EDUCATION (Neo Scientific Peer Reviewed Journal, 2023)
The current article discusses the main priorities of assessing project works given to students to accomplish at higher education. Mostly project works are evaluated according to language and presenting skills. The author is intended to add other transferrable skills those to improve project works quality and comprehension.